MICROSCOPIC CHANGES IN THE KIDNEYS AND MYOCARDIUM OF CHICKENS WITH INFECTIOUS LARYNGOTRACHEITIS - Борисевич, Б. В.; Лісова, В. В.; Криштоп, М. С. (Scientific Progress & Innovations, 2013)
The results of histological studies of kidneys and myocardium of chickens that died of infectious laryngotracheitis have been shown. It was found that circulatory disorders in the form of expansion and overflow of blood with blood vessels of body stroma, extra serosal capillary glomerulonephritis and degenerative changes and destruction of epithelial tubules are registered in the kidneys. In the myocardium the leading pathology was granular dystrophy of muscle cells. In addition, fragmentation and disorientation of muscle fibers was registered. In the epicardium and endocardium there were no microscopic changes.